The impact of Inflammatory Bowel Disease related fatigue on Health-Related Quality of Life: a qualitative semi-structured interview study. (December 2022) - Radford, Shellie J; Moran, Gordon W; Czuber-Dochan, Wladyslawa
Background: Fatigue is a frequently reported symptom of Inflammatory Bowel Disease (IBD), having a negative impact on Health-Related Quality of Life (HRQoL). Patients' experiences of this have not been researched in IBD. Methods: Semi-structured interviews were conducted with adults with Crohn's Disease from out-patient clinics in the United Kingdom. Interviews were audio-recorded and transcribed verbatim, then analysed using thematic analysis. Results: Fourteen participant interviews were conducted. Three key themes were identified: 1) 'The new normal' established through adaptation and acceptance; 2) 'Energy as a resource' describing attempts to better manage fatigue through planning and prioritising tasks; 3) 'Keeping healthy' encompasses participants' beliefs that 'good health' allows better management of fatigue. Conclusion: Participants establish a 'new' normality, through maintaining the same or similar level of employment/education activities. However, this is often at the expense of social activities. Further research is required to explore patient led self-management interventions in IBD fatigue.